Руководство по пересадке сердца у взрослых 2008–2011 - Jodie M. Fink; Tiffany Buda; Deanna Hartman; Kristin Ludrovsky; Jennifer Reese; Dave Pelegrin; Eileen Hsich; Nicholas Smedira; David O. Taylor; Randall C. Starling (Трансплантология (Москва), 2016)
.